EKSEKUSI SERTIFIKAT JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Muhammad Rutabuz Zaman (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstrak: This article aims to discuss the Fiduciary Guarantee after the Constitutional Court decision. So far, the meaning of the phrase